1985
DOI: 10.1111/j.1432-1033.1985.tb09137.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of calcium dissociation from calmodulin and its tryptic fragments. A stopped-flow fluorescence study using Quin 2 reveals a two-domain structure

Abstract: The kinetics of calcium dissociation from bovine testis calmodulin and its tryptic fragments have been studied by fluorescence stopped-flow methods, using the calcium indicator Quin 2. Two distinct rate proccsscs, each corresponding to the release of two calcium ions are resolved for calmodulin at both low and high ionic strength.The effect of 0.1 M KCI is to accelerate the slow process from 9.1 1.5 s f l to 24 k 6.0 s -l and to reduce the rate of the fast process from 650 s-l to 240 k 50 s -l at 25°C. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
95
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 37 publications
13
95
1
Order By: Relevance
“…It is therefore surprising that these ions should show an inverted binding preference in the case of calmodulin, although, as has been noted by Wang et al. [15], such an inversion is quite common for binding of these metals to small chelators.In a recent publication [14] we showed that fluorescence stopped-flow studies of CaM and its tryptic fragments were highly diagnostic in confirming the distribution of the binding sites into two classes for the interaction of CaM with calcium. This is because tryptic cleavage results in two fragments that each contain a pair of calcium binding sites, TRIC (residues…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…It is therefore surprising that these ions should show an inverted binding preference in the case of calmodulin, although, as has been noted by Wang et al. [15], such an inversion is quite common for binding of these metals to small chelators.In a recent publication [14] we showed that fluorescence stopped-flow studies of CaM and its tryptic fragments were highly diagnostic in confirming the distribution of the binding sites into two classes for the interaction of CaM with calcium. This is because tryptic cleavage results in two fragments that each contain a pair of calcium binding sites, TRIC (residues…”
mentioning
confidence: 74%
“…However, recent studies using l13Cd NMR [12], 43Ca NMR [22] and stopped-flow fluoresence measurements [14] with calmodulin and its tryptic fragments have shown that the high-affinity calcium (and cadmium) binding sites are, in fact, sites 111 and IV. Several other studies on CaM using techniques such as far-and near-ultraviolet CD measurements, 'H NMR and fluoresence measurements have shown that Tyr-99 and Tyr-138, which are located in domains 111 and IV, are most affected by binding of the first two calciums; this is also consistent with the idea that sites I11 and IV are, in fact, the high-affinity sites for calcium (for review, see [23]).…”
Section: Kinetics Of Cadmium and Terbium Dissociation From Calmodulinmentioning
confidence: 99%
“…CD [4], Ca2+ dissociation rates [17], NMR [l&-21]), calmodulin behaves as the sum of the two half molecules, with relatively little perturbation between side chains of residues located in the two globular domains of Ca2-TRlC and Ca2-TR2C when combined in Ca4-calmodulin. However, chemical modification of Lys-75 [22], Lys-77, Met-71, -72 and -76, and proteolytic sensitivity in the central sequence [l], are all modified by the binding of Ca2+, suggesting a Ca2+-dependent influence of the domain conformation on the properties of residues in the linking sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The complete kinetic scheme for the dissociation of Ca 2ϩ and peptide from a Ca 4 -CaM⅐peptide complex becomes unduly complex if the four Ca 2ϩ ions are considered to dissociate independently. It is reasonable, however, based on extensive experimental evidence for the dissociation kinetics of Ca 4 -CaM, to consider the Ca 2ϩ ions as dissociating in pairs, one pair from each domain (34). This assumption results in the Ca 2ϩ dissociation scheme shown in Fig.…”
Section: The Kinetic Modelmentioning
confidence: 99%
“…Ca 4 -CaM). Dissociation of this species is known to proceed almost exclusively via steps 3 and 6, and not via steps 9 and 8, as the C-terminal Ca 2ϩ ions dissociate about one hundred times slower from Ca 4 -CaM (C NCϪ ) than the N-terminal Ca 2ϩ ions (34). Correspondingly, we assume that dissociation of the C-terminal Ca 2ϩ pair from C NCP is always slower than dissociation of the N-terminal pair and have therefore eliminated step 12 and the subsequent steps 10 and 11.…”
Section: The Kinetic Modelmentioning
confidence: 99%